giải hộ e vs ah
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\left(2x-1\right)^2-\left(2x+3\right).\left(x-2\right)-2.\left(x+2\right).\left(x+5\right)\)
\(=\left(2x-1\right)^2-\left(2x+3\right).\left(x-2\right)-2.\left(x+2\right).\left(x+5\right)\)
\(=4x^2-4x+1-2x^2-3x+4x+6-2x^2-4x-10x-20\)
\(=4x^2-2x^2-2x^2-4x-3x+4x-4x-10x+1+6-20\)
\(=0-17x-13\)
\(=-17x-13\)
Ta thay \(x=-3\) vào
\(A=-17.\left(-3\right)-13=38\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(2x-1\right).\left(x+3\right)-x.\left(3+2x\right)=26\)
\(\Rightarrow2x^2+6x-x-3-3x-2x^2=26\)
\(\Rightarrow2x-3=26\)
\(\Rightarrow2x=29\)
\(\Rightarrow x=\frac{29}{2}\)
\(\left(2x-3\right)^2-4.\left(x+2\right).\left(x-2\right)-x=8\)
\(\Rightarrow4x^2-12x+9-4.\left(x^2-4\right)-x=8\)
\(\Rightarrow4x^2-12x+9-4x^2+16-x=8\)
\(\Rightarrow-13x+25=8\)
\(\Rightarrow-13x=-17\)
\(\Rightarrow x=\frac{17}{13}\)